Evaluasi Dampak Program Kawasan Rumah Pangan Lestari (KRPL) pada Kelompok Wanita Tani (KWT) Tunas Sejahtera di Kecamatan Blahbatuh, Kabupaten Gianyar - GUSTI NGURAH YOGI SUPUTRA; I GEDE SETIAWAN ADI PUTRA; I DEWA PUTU OKA SUARDI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Evaluation on the Impacts of Sustainable Food for Household Region Program (KRPL) on Female Farmers Association (KWT) Tunas Sejahtera Blahbatuh region, Gianyar regency. Food security is a state fulfillment and accessibility of food for every household, and such conditions can be met through the strengthening of food security at a household level. Female Farmers Association holds their agricultural activities based on propinquity, harmony, as well as mutual interest in utilizing farming resources aimed to increase both farms productivity as well as association members welfare. The scope of this research is to determine relevancy, efficiency, effectivity, as well as impacts of the projects and programs which were conducted systematically and objectively in accordance to the predetermined goals.Research findings show that the Sustainable Food for Household Region program in Blahbatuh area, Gianyar regency shows technical impact that falls into the progressive category with a score of 76,6%, while the economic impact falls into the intermediate category with a score of 66,9%, and the social impact falls into the progressive category as well with a score of 71,1%. Keywords: Evaluation on the impacts, food security program, female farmers association.